2019
DOI: 10.15836/ccar2019.184
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from ischemic heart disease and acute myocardial infarction in the City of Zagreb and Republic of Croatia 2001-2016

Abstract: Smrtnost od ishemijske bolesti srca i akutnog infarkta miokarda u Gradu Zagrebu i Republici Hrvatskoj od 2001. do 2016. godine Mortality from ischemic heart disease and acute myocardial infarction in the city of Zagreb and Republic of croatia 2001-2016 Izvorni znanstveni članak Original scientific paper

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Therefore, the survival benefit is governed by an entire chain of events starting from early recognition of symptoms to the prompt delivery of emergency services (EMS) and prompt transfer to a PPCI capable hospital [10,11]. Multiple studies, including the Zagreb study and Castiella et al, concluded that the biggest factor in pre-hospital delay was late recognition of symptoms and hence delay in seeking care, and this was independent of the effectiveness of the team or availability of the emergency services [12,13]. This observation was also shown in our study by the mean duration of chest pain being well over three hours.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the survival benefit is governed by an entire chain of events starting from early recognition of symptoms to the prompt delivery of emergency services (EMS) and prompt transfer to a PPCI capable hospital [10,11]. Multiple studies, including the Zagreb study and Castiella et al, concluded that the biggest factor in pre-hospital delay was late recognition of symptoms and hence delay in seeking care, and this was independent of the effectiveness of the team or availability of the emergency services [12,13]. This observation was also shown in our study by the mean duration of chest pain being well over three hours.…”
Section: Discussionmentioning
confidence: 99%